RAPID CONFIRMATION OF RABIES ANTIGEN IN FORMALIN-FIXED PARAFIN-EMBEDDED TISSUE BY IMMUNOPATHOLOGIC DIAGNOSIS - R. Wasito; Hastari Wuryastuti (Jurnal Sain Veteriner, 1996)
Skunks experimentally infected with street virus rabies intramuscularly were used to demonstrate rabies viral antigen in paraffin-embedded tissue by immunopathology diagnosis approach, the avidin biotin complex (ABC) method. The use of ABC method provides a simple and sensitive method to localize rabies virus antigen in formalin- fixed tissues. The results of the present study also demonstrated that a procedures using formalin-fixed parafin-embeded tissue and stained immunopathologicalH by the ABC method was an excellent method for both preservation of morfological details of ceils/tissues and demonstration of rabies virus antigen.